Revisiting the influence of individual factors on heat exchange during exercise in dry heat using direct calorimetry - Notley, S. R.; Lamarche, D. T.; Meade, R. D.; Flouris, A. D.; Kenny, G. P. (Experimental Physiology, 2019)
What is the central question of this study?